Corona discharge influence on micro-organisms - Scholtz, V. (Вопросы атомной науки и техники, 2005)
It is known, that the electric discharge can be used for micro-organism killing. Presented paper describes first qualitative results of atmospheric corona discharge influence on moulds (penicillium digitatum) experimental study. It seems, that the atmospheric corona discharge inhibits the fungi growth only. It seems, it does not kill both the living organism of mould and the spores. Preliminary experimental results indicate, that the ozone generated by atmospheric corona dicharge does not influence the fungi, too.